2018
DOI: 10.1002/adma.201804398
|View full text |Cite
|
Sign up to set email alerts
|

A High Current Density Direct‐Current Generator Based on a Moving van der Waals Schottky Diode

Abstract: nanogenerator can only output alternating current and the output current density is quite small (0.01-0.1 A m −2 ), [5] which limits its widespread applications. [6] Recently, the vertical movement between the metal and semiconducting polymer has been demonstrated to output intermittent current peaks with low current density (2.7-62.4 µA cm −2 ), [7] where the metal contacts with polymer periodically. On the other hand, the microscale direct current generator based on sliding between metal tip and semiconducto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
170
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(172 citation statements)
references
References 45 publications
2
170
0
Order By: Relevance
“…[19] Here, we shall also see that pulsing DC signal is generated but with similar output magnitude under linear reciprocal rubbing (Figure 2e,f). [7] The short-circuit J value is four times higher than the maximum dielectric AC that polymer-based TENG can possibly achieve in atmosphere (≈0.05 A m −2 ). The power output is maximized when R ≈ 146 kΩ, which approximates the internal resistance r of the system.…”
Section: Doi: 101002/aelm201900464mentioning
confidence: 94%
See 1 more Smart Citation
“…[19] Here, we shall also see that pulsing DC signal is generated but with similar output magnitude under linear reciprocal rubbing (Figure 2e,f). [7] The short-circuit J value is four times higher than the maximum dielectric AC that polymer-based TENG can possibly achieve in atmosphere (≈0.05 A m −2 ). The power output is maximized when R ≈ 146 kΩ, which approximates the internal resistance r of the system.…”
Section: Doi: 101002/aelm201900464mentioning
confidence: 94%
“…[1] The performance of TENGs is optimal only at high frequency due to the dielectric displacement current mechanism, while the environmental mechanical sources usually have frequencies lower than 10 Hz. [3,[5][6][7][8][9][10] The tribo-tunneling transport tip-enhanced current generation, as reported by Liu et al [3,6] using conductive-atomic force microscope (C-AFM), show that the tribo-tunneling current density ( J) output can be boosted by the nano-sized contact (tip radius R ≈ 30 nm) up to 10 6 A m −2 due to the enhanced electronic excitation and strong localized electric field E. It has been reported that a micro-tip (tip radius R ≈ 30 µm) sliding system produces a current density of 35 A m −2 while larger tip radius (R ≈ 100-300 µm) yields a current density of 10 A m −2 in the test probe sliding system. [3,[5][6][7][8][9][10] The tribo-tunneling transport tip-enhanced current generation, as reported by Liu et al [3,6] using conductive-atomic force microscope (C-AFM), show that the tribo-tunneling current density ( J) output can be boosted by the nano-sized contact (tip radius R ≈ 30 nm) up to 10 6 A m −2 due to the enhanced electronic excitation and strong localized electric field E. It has been reported that a micro-tip (tip radius R ≈ 30 µm) sliding system produces a current density of 35 A m −2 while larger tip radius (R ≈ 100-300 µm) yields a current density of 10 A m −2 in the test probe sliding system.…”
mentioning
confidence: 99%
“…sliding metal-insulator-semiconductor (MIS) structure, [14][15][16][17] the moving Schottky diode based on metal-semiconductor (MS) structure, [18][19][20] the triboelectric cell based on PN junction structure, [21][22][23] and other moving heterojunction nanogenerator. [24] Thundat and Liu et al realized an ultrahigh current density MIS nanogenerator due to quantum mechanical tunneling of the ultrathin natural oxide layer.…”
mentioning
confidence: 99%
“…[14][15][16] Lin et al designed a moving Schottky diode generator with high current density output which is based on the built-in electric field separation. [18] Zhang and Xu et al reported a direct-current triboelectric cell by sliding PN junction and indicated that its mechanism may be the formation of electron-hole pairs. [22] It is true that these novel generators with continuous, high-density, and direct-current output characteristics have shown great interest and potential, but the power generation mechanisms of them remain to be extensively studied.…”
mentioning
confidence: 99%
“…However, low electric current densities and short product lifespans of current nanogenerators have blocked real applications of nanogenerators explored so far 3,6,18 .…”
mentioning
confidence: 99%